Ultrastructural Characterization of Noradrenergic Axons and Beta-Adrenergic Receptors in the Lateral Nucleus of the Amygdala - Farb, Claudia; Chang, William; LeDoux, Joseph (Frontiers in Behavioral Neuroscience, 2010)
Norepinephrine (NE) is thought to play a key role in fear and anxiety, but its role in amygdala-dependent Pavlovian fear conditioning, a major model for understanding the neural basis of fear, is poorly understood. The lateral nucleus of the amygdala (LA) is a critical brain region for fear learning and regulating the effects of stress on memory. To understand better the cellular mechanisms of NE and its adrenergic receptors in the LA, we used antibodies directed against dopamine beta-hydroxylase (DβH), the synthetic enzyme for NE, or against two different isoforms of the beta-adrenergic receptors (βARs), one that predominately recognizes neurons (βAR 248) and the other astrocytes (βAR 404), to characterize the microenvironments of DβH and βAR. By electron microscopy, most DβH terminals did not make synapses, but when they did, they formed both asymmetric and symmetric synapses. By light microscopy, βARs were present in both neurons and astrocytes. Confocal microscopy revealed that both excitatory and inhibitory neurons express βAR248. By electron microscopy, βAR 248 was present in neuronal cell bodies, dendritic shafts and spines, and some axon terminals and astrocytes. When in dendrites and spines, βAR 248 was frequently concentrated along plasma membranes and at post-synaptic densities of asymmetric (excitatory) synapses. βAR 404 was expressed predominately in astrocytic cell bodies and processes. These astrocytic processes were frequently interposed between unlabeled terminals or ensheathed asymmetric synapses. Our findings provide a morphological basis for understanding ways in which NE may modulate transmission by acting via synaptic or non-synaptic mechanisms in the LA.